A Mini Review on Exosomal Mediators in Endometriosis: From Pathogenesis to Diagnostic and Therapeutic Avenues - Melika Izadpanah (Journal of Ardabil University of Medical Sciences)
Endometriosis is a long-term health condition that is known as a significant factor in women's infertility issues nowadays. Since many factors contribute to the development of this disease and because diagnosis is difficult and typically happens late in the progression of the disease, early detection is especially crucial. Extracellular micro vesicles called exosomes have diverse biological molecules and can alter the behavior of recipient cells, influencing angiogenesis, fibrosis, and inflammation. Exosomes are significant in cell communication and could act as new biomarkers for early detection of endometriosis. Hence, exploring and comprehending the impact of exosomes on the development of endometriosis can create opportunities for studying potential diagnostic biomarkers and targeted therapeutic interventions to prevent the advancement of the condition. This article delves into new approaches to diagnose and treat endometrial disorders by highlighting the various functions of exosomes in endometriosis.